Discovery of novel interacting partners of PSMD9, a proteasomal chaperone: Role of an Atypical and versatile PDZ‐domain motif interaction and identification of putative functional modules. Issue 1 (6th June 2014) - Sangith, Nikhil; Srinivasaraghavan, Kannan; Sahu, Indrajit; Desai, Ankita; Medipally, Spandana; Somavarappu, Arun Kumar; Verma, Chandra; Venkatraman, Prasanna
Abstract : PSMD9 (Proteasome Macropain non‐ATPase subunit 9), a proteasomal assembly chaperone, harbors an uncharacterized PDZ‐like domain. Here we report the identification of five novel interacting partners of PSMD9 and provide the first glimpse at the structure of the PDZ‐domain, including the molecular details of the interaction. We based our strategy on two propositions: (a) proteins with conserved C‐termini may share common functions and (b) PDZ domains interact with C‐terminal residues of proteins. Screening of C‐terminal peptides followed by interactions using full‐length recombinant proteins, we discovered hnRNPA1 (an RNA binding protein), S14 (a ribosomal protein), CSH1 (a growth hormone), E12 (a transcription factor) and IL6 receptor as novel PSMD9‐interacting partners. Through multiple techniques and structural insights, we clearly demonstrate for the first time that human PDZ domain interacts with the predicted Short Linear Sequence Motif (SLIM) at the C‐termini of the client proteins. These interactions are also recapitulated in mammalian cells. Together, these results are suggestive of the role of PSMD9 in transcriptional regulation, mRNA processing and editing, hormone and receptor activity and protein translation. Our proof‐of‐principle experiments endorse a novel and quick method for the identification of putative interacting partners of similar PDZ‐domain proteins from the proteome and for discovering novel functions. Abstract : The structure and functions of PSMD9, a proteasomal chaperone, are uncharacterized. PDZ‐like domain of PSMD9 may recognize C‐terminal residues in proteins. Using conserved C‐terminal motifs in human proteome, we identify novel binding partners. hnRNPA1, GH, IL6‐receptor, S14 and E12 interact with PSMD9 via a specific C‐terminal motif. We predict and confirm residues in the PDZ domain that are involved in this interaction.